ANALISIS PRODUKTIFITAS HOME INDUSTRI TAHU DI DESA MOTODUTO KECAMATAN BOLIYOHUTO - Sri Hantuti Paramata; Nur Eng Mokodompit; Nesta Lihu (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2019)
This research was carried out at the manufacturing industry located in the “Cipta Sari” motoduto village of Boliyohuto sub-district, aiming to (1) to analyze the amount of tofu production costs, (2) to analyze how much the tofu industry income, and (3) to analyze the feasibility level of the tofu industry in the village of Motoduto, Boliyohuto District. This research is qualitative research. Analysis in which this research is carried out is only descriptive which gives an overview of the problems to be examined in the form of numbers. From the results of the study, the amount of fixed costs of Cipta Sari tofu industry is Rp.27,000,000,- and the amount of variable costs is Rp.93,610,000. The amount of revenue / income of Cipta Sari tofu industry comes from the sale of tofu and tofu pulp, which is Rp.144,000,000. From the amount of fees and receipts / revenues above, it can be seen the total cost of Rp.120,610,000, and the profit amount of Cipta Sari’s tofu industry which is Rp.23,390,000,- and the teasibility value of Cipta Sari’s tofu industry is 1,19 and said to be feasible to maintain, because the value of the Revenue Cost Ratio (RCR) is > 1. Keywords : Analysis, Productivity, Home Industry.